Pengaruh Bantuan Modal Usaha Terhadap Pendapatan Pedagang Tradisional pada Pasar Meeto Kabupaten Kolaka Utara - Ninik Endang Purwati (Business UHO: Jurnal Administrasi Bisnis, 2019)
This study aims to determine the effect of venture capital assistance on the income of traditional traders in the North Kolaka Meeto Market. The population in this study were all traditional traders in the Meeto Market who were given capital assistance of 60 people. Sampling is done by sample cluster sampling, where each population is grouped according to the type of business being operated. To obtain a representative sample size of each type of business operated, 50% of the population was determined. So that the samples in this study were 30 respondents consisting of: 13 fish sellers, 8 chicken sellers, 9 people selling groceries. Analysis of the data used in this study is a qualitative analysis used to analyze descriptively the effect of venture capital assistance on the income of traditional traders and quantitative analysis used to analyze quantitatively about the income of traditional traders in the Meeto Market of North Kolaka Regency using simple linear regression. and discussion, The Effect of Business Capital Assistance on Traditional Trader Income that the relationship between venture capital assistance and income shows a positive and significant relationship. Meanwhile, the magnitude of the contribution of venture capital assistance to income amounted to 0.9226 or 92.26 percent of the income of traditional traders.